The Interface Between the Christian Concept of the Common Good, the African Concept of Ubuntu, and Politics - PAUL ABUDULAI YELINJE (African Theological Journal for Church and Society)
The subject of Christianity and politics has generated numerous debates with varying scholarly strands. This centuries-long contention has resulted in three main perspectives on how Christians should engage in politics. One viewpoint advocates total involvement of Christians in politics (the involvement view), another supports a complete separation between Christianity and politics (the separation view), and the third promotes transformation (the transformation view). This work does not cover these main strands, as the paper aims to avoid entering into existing controversies. Instead, this paper explores the intricate interplay between the Christian concept of the Common Good, the African philosophy of Ubuntu, and their intersection within the realm of politics. Both concepts emphasize communal well-being, social harmony, and ethical responsibility towards others. The Christian understanding of the common good highlights the importance of promoting justice, solidarity, stewardship, and the well-being of all members of society. Ubuntu, deeply rooted in African tradition, stresses interconnectedness, compassion, and the intrinsic value of every individual within the community. This paper delves into how these philosophical frameworks converge and diverge in their approaches to addressing societal challenges and shaping political discourse. It examines how Christian teachings on love, justice, and service can inform political decision-making and policy formulation to advance the common good. Likewise, it explores how Ubuntu's emphasis on empathy, inclusivity, and human dignity can influence governance structures and foster a sense of shared humanity in political processes.